Reenvisioning velocity reversal as a diversity of hydraulic patch behaviours. Issue 13 (6th March 2016) - Strom, Michael A.; Pasternack, Gregory B.; Wyrick, Joshua R.
Abstract: Past research investigated the surpassing of mean velocity at riffle cross sections by that at pool cross sections for flows up to bankfull, termed 'velocity reversals', to understand one mechanism by which riffle–pool relief is maintained. This study reenvisioned the classic velocity reversal by documenting stage‐dependent changes to the locations of peak velocity without cross sections. Instead, the dynamics of peak velocity patches were considered for flows spanning 0.2 to 22 times bankfull discharge through the use of a high‐resolution DEM and two‐dimensional hydrodynamic modelling. A remarkable diversity in peak velocity patch behaviour was found across discharges, including gradual expansion and shifting as well as abrupt disappearance and emergence relative to the low‐flow patch locations. These behaviours blended together to varying degrees to produce many reversals in peak velocity across morphological units, but it took substantially higher than bankfull discharge for peak velocities to move from riffles and chutes to fast glides and pools. The discharges at which reversals occurred among morphological units were significantly higher for the valley‐confined reach than for the anastomosing reach. Copyright © 2016 John Wiley & Sons, Ltd.